FOR THE SAKE OF SAVING A VIABLE LIFE: ARGUMENTS FOR COURT ORDERS PREVENTING TERMINATION OF PREGNANCY PROCEDURES AND THE FORCING OF IN UTERO SURGERY IN SURROGACY AGREEMENTS (The Pretoria Student Law Review, 2021)
This article addresses two questions, namely, whether a court can prevent a surrogate mother from terminating a pregnancy and, secondly, whether a court can force a surrogate to undergo in utero surgery. To introduce the reader to a situation where the arguments of this article could become relevant, we add a hypothetical case. A couple discover that they both have cancer. Their cancer treatment will result in them becoming sterile. Therefore, they decide to enter into a full surrogacy agreement, that is, where both their gametes are implanted in a third party’s uterus. Before the cancer treatment begins, they donate the required genetic material. No further conception by way of full or partial surrogacy is possible. Just before birth it is discovered that the foetus has a severe defect. The surrogate mother wants to terminate the pregnancy, despite the fact that the defect may be corrected in utero. The biological parents apply to court asking the court to: (1) prevent the surrogate mother from terminating the pregnancy; (2) compel the surrogate mother to undergo in utero surgery.
Keywords: surrogate mother; terminating a pregnancy; utero surgery; court; third party’s uterus; full or partial surrogacy